The assessment of multicultural strength: Design and validation of an Openness to the Other Affective Domain Inventory - Cosentino, Alejandro César (2014)
The classification of character strengths and virtues by Peterson and Seligman (2004) includes 24 strengths and 6 virtues. Although the development of this classification was inspired by diverse cultural traditions, no one strength or virtue centrally focused on cultural aspects. Fowers and Davidov (2006) have proposed a new multicultural strength or virtue termed as openness to the other. We developed the Openness to the Other Affective Domain Inventory (OADI), a new 6-item measurement instrument to assess affective attraction to the other, that is, fascination with or attraction to culturally diverse others, and affective aversion to the other, that is, distrust of or disgust with culturally diverse others. The results showed evidence of acceptable reliability, incremental and convergent validity, validity with an external criterion, and known group validity for the OADI. Moreover, a confirmatory factor analysis yielded an excepted two-factor model that corresponded to the attraction and aversion dimensions.